Breaking the cycle: Systematic review of perinatal interventions for parents at risk of child removal - Esther Ariyo; Victoria Awortwe; Ebenezer Cudjoe (PLoS ONE, 2025)
This systematic review examined the effectiveness of perinatal interventions aimed at preventing infant removals, with attention to service features, implementation barriers, and enablers. We searched six electronic databases and 15 relevant websites for peer reviewed studies published between 2014 and 2024. Eligible studies evaluated interventions targeting pregnant parents at risk of having another child removed and reported on infant removal outcomes. Independent reviewers screened studies using Covidence. A total of 256 records were obtained, of which six peer reviewed studies covering eight interventions, involving 3,254 pregnant women and 20 professionals met the inclusion criteria. Three studies included comparison groups, including only one randomized controlled trial. Five studies assessed program-level interventions, and one study evaluated a policy change. Risk of bias was assessed using the Mixed Methods Appraisal Tool (MMAT). Two of the three comparative studies indicated that targeted interventions may help reduce infant removals. Four of the six studies highlighted that trauma-informed, relationship-based, and multidisciplinary approaches delivered during pregnancy were associated with reductions in infant removals and improvements in maternal wellbeing, housing stability, substance use, and service engagement. Facilitators of successful implementation included continuity of care, culturally safe and non-judgmental support, and flexible services tailored to family needs. Common barriers were late referrals, limited intervention timelines, mistrust of services particularly among families with prior removals and insecure funding that constrained scale and sustainability. Despite generally positive outcomes, the evidence base remains weak due to small samples, limited diversity, lack of comparison groups, and short follow-up periods. This first systematic review of perinatal interventions for preventing infant removals highlights the need for long term, inclusive, comparative research. It underscores the importance of embedding early, holistic support in routine services and offers valuable insights for policy and practice on supporting parents with complex needs within the child protection system.